Influence of variously modified surface of aluminium alloy on the effect of pulsating water jet - Klich, Jiri (Strojniški vestnik, 2017)
Erosion effects of a pulsating water jet impinging the surface of aluminium alloy samples pre-treated by various techniques (rough and fine milling, planing and rolling) were studied. The influence of the initial surface topography on the final topography of the sample exposed to the pulsating water jet was investigated. Based on roughness parameter Ra erosion of surface layers was analysed and discussed in relation to the traversing speed of the jet. It was found that initial surface pre-treatment have a significant impact on the final topography of the surface affected subsequently by pulsating water jet. Surfaces, whose properties are significantly affected by the action of some machining processes (i.e. milling) show much greater resistance to pulsating water jet than unpaved surfaces (i.e. rolling) and surfaces have smaller roughness. While milled (rough or fine) or planed surface roughness has approximately the same increase of Ra parameter, only rolled surfaces are up to 150 times rougher after pulsating water jet treatment. This is due to the small hardening of the surface layers and reduced durability against pulsating water jet in comparison with others investigated techniques. The highest roughness was achieved on all pre-treated surfaces at the lowest speeds, because the pulsating water jet affects the surface for a longer time.
Keywords: aluminijeve zlitine; aluminium alloy; erozija materiala; obdelava površine; pulzirajoči vodni curek